Effects of Modest Hypoxia and Exercise on Cardiac Function, Sleep-Activity, Negative Geotaxis Behavior of Aged Female Drosophila - Li, Qiu Fang; Wang, Hui; Zheng, Lan; Yang, Fan; Li, Han Zhe; Li, Jin Xiu; Cheng, Dan; Lu, Kai; Liu, Yang (Frontiers in Physiology, 2020)
Mild normobaric hypoxia (NH) and modest exercise have multiple beneficial effects on health, but the changes in physiological function induced by NH and/or exercise remain unclear. The purpose of this investigation was to examine the specific effects of NH and/or exercise on cardiac function and myocardial structure and behavior including sleep-activity and negative geotaxis in aged Drosophila. We also assessed the survival rate of flies after hypoxia and/or exercise. One-thousand wild-type w1118 virgin female flies were randomly divided into four groups and treated with NH and/or exercise from ages three to six weeks. We found that exercise remarkably delayed the decline of actin and myosin and the age-related changes in cardiac structure, improved abnormal cardiac contraction, and enhanced the cardiac pumping force by inducing cardiac hypertrophy and delaying deterioration of cardiac contractility and diastolic compliance, and improved abnormal heart contraction. NH also increased the content of actin and myosin, but induced a decrease in heart diameter and heart rate, as well as an increase in the number of mitochondria and deeper sleep, which may be the manifestation of energy saving under long-term hypoxia. Both NH and exercise improved sleep quality and climbing ability of aged flies, as well as extended the maximum life span, which shows the benefits of hypoxia and exercise. Finally, the superposition of NH and exercise did not impart any obvious physiological and behavior improvement. Therefore, it is necessary to further explore the appropriate combination of hypoxia and exercise.